Achieving myoblast engraftment into intact skeletal muscle via extracellular matrix - Dohi, Kitora; Manabe, Yasuko; Fujii, Nobuharu L.; Furuichi, Yasuro (Frontiers in Cell and Developmental Biology, 2025)
Cell therapy of skeletal muscles is a promising approach for the prevention of muscular diseases and age-related muscle atrophy. However, cell transplantation to treat muscle atrophy that does not involve disease, such as sarcopenia, is considered impossible because externally injected cells rarely engraft into non-injured muscle tissue. Additionally, skeletal muscle-specific somatic stem cells, called satellite cells, lose their ability to adhere to tissue after being cultured in vitro and transforming into myoblasts. To overcome these hurdles, we explored using extracellular matrix (ECM) components to create a niche environment conducive for myoblasts during transplantation. We demonstrated that myoblasts mixed with ECM components can be engrafted into intact skeletal muscle and significantly increase muscle mass in a mouse model. These findings implicate cell transplantation therapy as a viable option for the treatment of sarcopenia. The findings will inform advancements in regenerative medicine for skeletal muscles.